The Urgency of Riyaya Undhuh-Undhuh Tradition in Building Tolerance for Inter-Religious Life in the Mojowarno Community - Eliana Meidi Asiafi; Dwi Retnani Srinarwati (Budapest International Research and Critics University, 2022)
Riyaya Undhuh-Undhuh is a tradition of the Jawi Wetan Mojowarno Christian Church. It gives thanks to God for the rice harvest by combining Javanese traditions which involve various religious adherents. Inter-religious tolerance is very much needed in a society that has different religions. The objectives of the research are (1) to find out the process of implementing Riyaya Undhuh-Undhuh tradition at GKJW Mojowarno; (2) to find out the tolerance between religious communities in the life of the people in Mojowarno; (3) to find out the role of tradition on inter-religious tolerance in the Mojowarno community. This research used a descriptive qualitative approach. The data collected was about (1) the implementation of Riyaya Undhuh-Undhuh tradition; (2) inter-religious tolerance in the life of the Mojowarno community; (3) the role of tradition towards inter-religious tolerance in Mojowarno with data sources from pastors, congregations’ assemblies, communities, and various religious adherents. Data collection techniques used interviews, observation with participant observation techniques, and documentation. The data were analyzed by qualitative analysis with the stages of data collection, reduction, presentation, conclusion. The validity of the data was obtained by using technical triangulation and source triangulation. The results of this research indicated the role of the Riyaya Undhuh-Undhuh tradition as tolerance between religious communities in the Mojowarno community.